Pore-water salinity measurements in surface sediments within DynaCom experimental islands and saltmarsh enclosed plots at different elevation levels, Spiekeroog, Germany, 2023-01 to 2023-08 - Pieck, Daniela; Schilken, Esther; Slivensky-Graf, Cassidy; Weyel, Niklas; Dietrich, Kathrin; Lõhmus, Kertu; Hillebrand, Helmut; Kleyer, Michael; Zielinski, Oliver; Wollschläger, Jochen; Badewien, Thomas Henry (PANGAEA, 2025)
Data presented here were collected between January 2023 to August 2023 within the research unit DynaCom (Spatial community ecology in highly dynamic landscapes: From island biogeography to metaecosystems) of the Universities of Oldenburg, Göttingen, and Münster, the iDiv Leipzig and the Nationalpark Niedersächsisches Wattenmeer. Experimental islands and saltmarsh enclosed plots were created in the back barrier tidal flat and in the saltmarsh zone of the island of Spiekeroog. Sediment samples for the determination of pore-water salinity were taken bi-/monthly in surface sediments (0-3 cm depth) of the experimental plots. Samples were taken between 3 hours before and 3 hours after low tide. Samples were stored dark and cool (8°C) until measurement. Samples were measured in the laboratory within two months after sampling according to DIN ISO 11265:1997-06. In the laboratory, sediment samples for the determination of pore-water salinity were weighed in pre-weighed Falcon™ 50 mL conical centrifuge tubes (10 g sediment on average, depending on sand content). After one month of air-drying samples were re-weighed to determine dry weight and therefore the loss in weight. Ultrapure water was added to the tubes and were homogenized using a pestle. Salinity was measured directly in the tubes with a HQ40D Digital two channel multi meter and a pre-calibrated Intellical CDC401 field 4-poles graphite conductivity cell (Hach Lange GmbH, Germany). Post-processing of measured values were done using MATLAB (R2024b). Quality control was performed by (a) visually checks, and hence (b) the classification into quality control flags using quality check algorithms.
Keywords: BEFmate; biodiversity - ecosystem functioning; DynaCom; experimental islands; Field experiment; Metacommunity; pore-water salinity; salt marsh; SCO; Spiekeroog; Spiekeroog Coastal Observatory